Nexus between Institutional Quality and Capital Inflows at Different Stages of Economic Development - Athari, Seyed Alireza; Adaoglu, Cahit (Wiley, 2019)
We examine the determinants of capital inflows for a global sample of countries at various stages of economic development, namely factor-, efficiency-, and innovation-driven stages. We investigate the effect of institutional quality on capital inflows. The magnitude of institutional quality effect depends on the stage of economic development. Both public and private institutional qualities positively affect capital inflows in efficiency- and innovation-driven countries. Specifically, corporate ethics and accountability are pull factors for capital inflows at all stages.
Keywords: Flow; Poor; Rich